Driven apart: womens employment equality and child care in canadian public policy - Timpson, Annis MayMarshall (Toronto: UBC Press, 2001)
Contents: The double-edged nature of womens employment inequqlity. Citizenship, motherhood, and employment in the wartime and welfare states. The royal commission on the status of women. A just society?. The trudeau governments response to the royal commission on the status of women
Keywords: Feminismo - América Latina